Multi-scale modelling of biomass pyrolysis processes - Sharma, Abhishek; Pareek, Vishnu; Zhang, D. (Elsevier, 2012)
Thermo-chemical decomposition of biomass to bio-energy via pyrolysis is a complex process. Several pyrolysis models have been proposed for predicting the yields of desired components as a function of operating conditions. These models, however, have not considered the overall effect of process parameters and hence, are not capable of accurately predicting product yields with variation in operating conditions. Consequently, there is requirement for developing comprehensive multi-scale models for studying the combined impact of various parameters during biomass conversion. In this study, a detailed particle scale model has been developed by coupling two-stage reaction mechanism with transport phenomena to account for the combined impact of different parameters on the conversion process. Simulations have been conducted for validating this model and analysing the effect of operating temperature and particle size variation on the biomass conversion time. Based on results, it has been concluded that both particle size and operating temperature affects the rate of biomass decomposition and it is required to optimally choose these parameters with other operating conditions for getting complete conversion of biomass.